(untitled) (UUM Journal of Legal Studies, 2026)
Social entrepreneurship, a fast-developing sector in Malaysia, has the capacity to contribute to the social development and economic growth of the nation. Whilst social enterprises in Malaysia have made considerable impacts in terms of enhancing community welfare, driving sustainable development, and fostering inclusive growth, there are still challenges and obstacles that impede their continued development. This article argues that one of the obstacles to the advancement and growth of the social enterprise sector is the government policy on the accreditation of social enterprises in Malaysia. Since its introduction in 2017, the Malaysian government’s policy on the accreditation of social enterprises has been revised four times. This article aims to conduct a critical evaluation of the accreditation policy relating to social enterprises by exploring its development and evolution, followed by highlighting its shortcomings and areas for improvement. This article employs a doctrinal legal study using the exploratory research design and interpretive qualitative content analysis to analyse policy documents related to the accreditation of social enterprises in Malaysia. After examining the effectiveness of the current accreditation policy for social enterprises in Malaysia, this study finds that it is hindered by frequent changes, subjective and ambiguous criteria, and a lack of legislative support, thus raising concerns about issues related to transparency, accountability, and unclear justifications for the introduction of various categories of social enterprises. These findings make a case for legislative intervention to provide greater clarity, certainty, transparency, and accountability on the crucial aspects of social enterprise governance.